WRITING LESSONS IN GRADE 1 INDONESIAN THEMATIC TEXTBOOKS: A CONTENT ANALYSIS - Sulfasyah, Sulfasyah; Bahri, Aliem; Saleh, Sitti Fithriani (Indonesian Journal of Applied Linguistics, 2018)
The Ministry of Education and Culture of Indonesia has launched a new curriculum, the 2013 Curriculum. It promotes a transition from a traditional learning approach to a more progressive one that appears to reflect a constructivist approach. To ensure the successful implementation of the new curriculum, the Ministry produced compulsory textbooks for teachers and students. This study is aimed at revealing the presentation of writing lessons in the compulsory textbooks for Grade 1 that reflects the underlying theory of the 2013 Curriculum. The study analysed the frequency of writing lessons in the textbooks. It also analysed the types and the focus of writing activities in the lessons by using a content analysis. The sample consisted of eight textbooks of Grade 1. Each book consists of 24 lessons. Therefore, 192 lessons were analysed in this study. The results of the content analysis show that writing lessons in the textbooks, to a great degree, are still influenced by a traditional view of learning, especially those in the first two books used in Semester 1. In fact, the new curriculum appears to promote a constructivist approach. The findings suggest that there was inconsistency between the theory underpinning the writing lessons in the textbooks and the theory required by the 2013 Curriculum. In light of these findings, the study considers practical implications to increase the teaching of writing in Grade 1 based on the 2013 Curriculum Framework.